Peran Pemuda dalam Memperkuat Kebhinekaan di SMK Negeri 4 Gorontalo: Pengabdian - Zulaecha Ngiu; Yuli Adhani; Abdul Nawan Igirisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The community service program conducted by lecturers and students of the Civic Education (PPKn) Undergraduate Program at Gorontalo State University at SMK Negeri 4 Gorontalo aimed to foster students’ awareness and appreciation of diversity values through educational, reflective, and participatory approaches. This program was designed as a strategic effort to strengthen students’ understanding, attitudes, and behaviors toward cultural, religious, and social diversity within the school environment. The implementation method employed a participatory research approach based on observation and the distribution of a diversity questionnaire covering cognitive, affective, and conative dimensions. The questionnaire was used to map students’ perceptions of tolerance, solidarity, and attitudes toward differences, which then served as the foundation for organizing interactive activities such as national dialogue sessions. The evaluation results indicated that students of SMK Negeri 4 Gorontalo demonstrated a positive understanding of diversity values, with the majority showing openness, tolerance, and readiness to actively contribute to maintaining unity. Nevertheless, it was found that affective and conative aspects still required reinforcement so that diversity values would not only be understood cognitively but also internalized and practiced in daily life. Overall, this community service activity successfully enhanced multicultural awareness and strengthened students’ national character as young generations committed to unity in diversity.